High-dose oral atorvastatin pretreatment of patients undergoing cardiac surgery protects atrial muscle against simulated ischaemia–reperfusion injury. (22nd September 2015) - Rees, PSC; Ludman, AJ; Teoh, KL; Bognolo, G; Kolvekar, S; Yap, J; Lawrence, D; Hayward, M; Hausenloy, DJ; Yellon, DM
Abstract : Introduction: Experimental animal studies suggest that acute treatment with "statins" reduces myocardial infarct size. However, this cardioprotective effect is lost with chronic statin therapy but can be recaptured with an acute high dose of statin therapy given before infarction. We hypothesised that pretreatment with high-dose atorvastatin confers additional cardioprotection in patients undergoing elective cardiac surgery, when compared with standard statin therapy. Methods: Patients undergoing elective cardiac surgery were randomly assigned to the following treatment groups: (1) control: patients received their usual statin therapy before cardiac surgery; (2) patients were given high-dose atorvastatin (160 mg) 12 h before cardiac surgery in place of their usual statin therapy. During cardiac surgery, right atrial appendages were harvested from which atrial trabeculae were dissected. The isolated atrial trabeculae were then suspended in an organ bath and subjected to 90 minutes hypoxia followed by 120 minutes rexoygenation in order to simulate ischaemia–reperfusion injury. At the end of the reoxygenation period, the recovery of baseline contractile function was determined. A group of atrial trabeculae harvested from control patients taking their usual statin therapy was subjected to a standard hypoxic preconditioning protocol comprising 3 minutes hypoxia followed by 7 minutes reoxygenation before the index hypoxic episode. Results: Atrial trabeculae harvested from control patients taking standard statin therapy (N = 15 patients) were shown to recover 35.2 ± 1.1% of baseline contractile function. Interestingly, there was a significant improvement in the recovery of baseline contractile function in atrial trabeculae taken from patients (N = 10 patients) pretreated with the high dose of oral atorvastatin (54.0 ± 1.5% with atorvastatin vs 35.2 ± 1.1% in control; p<0.001). This level of cardioprotection was comparable with that achieved by hypoxic preconditioning of atrial trabeculae (used as a positive control) and harvested from patients on standard statin therapy (N = 12) (55.7 ± 2.7% with hypoxic preconditioning vs 35.2 ± 1.1% in control; p<0.001). Conclusions: Pretreatment with high-dose oral atorvastatin improves recovery of function from hypoxia–reoxygenation injury over and above that obtained by standard statin therapy in patients undergoing elective cardiac surgery.